GATA2 Deficiency in Adult Life Is Characterized by Phenotypic Diversity and Delayed Diagnosis - Shamriz, Oded; Zahalka, Naseem; Simon, Amos J.; Lev, Atar; Barel, Ortal; Mor, Nofar; Tal, Yuval; Segel, Michael J.; Somech, Raz; Yonath, Hagith; Toker, Ori (Frontiers in Immunology, 2022)
The transcription factor GATA2 plays a key role in the survival and self-renewal of hematopoietic stem and progenitor cells. Autosomal dominant mutations in GATA2 cause a broad spectrum of heterogeneous phenotypes. Here, we present our experience with GATA2 deficiency in a retrospective multicenter analysis of computerized medical records of adult patients (age ≥18 years) treated between 2018 and 2022 at Shaare Zedek Medical Center in Jerusalem and Sheba Tel-Hashomer Medical Center in Ramat Gan, Israel. Two male and two female patients with GATA2 deficiency were identified. Three of the patients presented with symptoms in adult life and all patients were diagnosed as adults. Age at presentation was 10.5-36 years and age at diagnosis 24-47 years. Diagnosis was delayed in all patients by 1-24.5 years. The phenotypic diversity was notable. Patients presented with myelodysplastic syndrome (n=2), pulmonary alveolar proteinosis (n=1), and recurrent viral (n=1), bacterial (n=3), and mycobacterial (n=1) infections. Bone marrow biopsy revealed cytogenetic abnormalities in one patient (monosomy 7). Patients were diagnosed by exome sequencing (n=3) and Sanger sequencing of the coding exons in GATA2 (n=1). Novel heterozygous GATA2 variants (c.177C>A, p.Y59* and c.610dup, p.R204PfsTer78) were identified in two patients. Immune workup revealed B cell lymphopenia and monocytopenia in all patients. One patient died from overwhelming sepsis despite all patients being treated with antibiotics and anti-mycobacterials. Our cohort highlights the phenotypic diversity, late presentation, and delayed diagnosis of GATA2 deficiency. Increased awareness of this primary immune deficiency presenting in adult life is needed and should involve a high index of suspicion.